CORRECTION OF AGE CHANGES IN THE FACIAL SKIN WITH ACUPUNCTURE LIFTING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Acupuncture is a method, the essence of which is to irritate peripheral nerve endings by inserting needles into these active zones. In turn, restoring endothelial dysfunction. Endothelial dysfunction is a central link in pathogenesis. Endothelial cells create a barrier between blood and tissues, perform a number of important regulatory functions, synthesizing and secreting a large number of various biologically active substances. Facial wrinkles are an integral part of the aging process, but many people strive to reduce their visibility and slow the appearance of new wrinkles. Among the various methods offered by the cosmetic industry, acupuncture has emerged as one of the highly effective treatments. In this article, we'll look at what acupuncture is and how it can be used to treat facial wrinkles.